1979
DOI: 10.1136/adc.54.6.448
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial asthma in Nigerian children.

Abstract: SUMMARY Clinical and laboratory studies on bronchial asthma in 200 Nigerian children who were seen during a 2k-year period in Ibadan are described. Contrary to reports that the condition is rare in African children, after pulmonary tuberculosis, asthma is the next most common chronic chest disease in Ibadan. While many features of the disease are similar to those seen elsewhere, skin tests indicate that ascaris is the most common antigen associated with asthma, followed by Dermatophagoides pteronyssinus.Bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
0
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 14 publications
9
22
0
1
Order By: Relevance
“…This may be partly due to the fact that most children with asthma tend to present with symptoms by six years of age 3,5 and also children of this age group are of school age with likelihood of exposure to trigger factors at school such as exercise, dust and contagious viral respiratory tract infections. Many of these children may be walking to school which may serve as a form of exercise and hence trigger asthma attack.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be partly due to the fact that most children with asthma tend to present with symptoms by six years of age 3,5 and also children of this age group are of school age with likelihood of exposure to trigger factors at school such as exercise, dust and contagious viral respiratory tract infections. Many of these children may be walking to school which may serve as a form of exercise and hence trigger asthma attack.…”
Section: Discussionmentioning
confidence: 99%
“…However not all children who experience recurrent wheezing will go on to have persistent asthma in later childhood 4 . Aderele 5 reported 63% of asthmatic children seen in Ibadan had their first attack before the age of three years and 97% of study population were under the age of 5years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have since shown that asthma is far more common in the Nigerian child than previously thought 3 and that it can start at any age. 4 The challenges of diagnosing asthma in this group of infants are enormous and have been repeatedly documented.…”
Section: Discussionmentioning
confidence: 99%
“…2 It was initially reported to be rare among African children but studies in Nigeria have shown that asthma is far more common than previously thought, being second to pulmonary tuberculosis as the next most common chronic chest disease in children. 3 Asthma can start at any age and is suggested by a chronic or recurrent nature, frequently associated with family history of allergic sensitization and atopic dermatitis. 4 The diagnosis of asthma in infants is more difficult than in older children or adults.…”
Section: Introductionmentioning
confidence: 99%